Dodder (Cuscuta reflexa Roxb.), a severe parasitic weed on fennel (Foeniculum vulgare Mill.) - BHATI, D S (Journal of Spices and Aromatic Crops, 1994)
A survey on weed infestation in fennel (Foeniculum vulgare) undertaken in Tonk District of Rajasthan, India during rabi season of 1986-87, indicated that the parasitic weed Cuscuta reflexa was observed in 6 fields among the 11 fields surveyed. In infested fields, 70.70 to 23.04 per cent plants were parasitised. The seed yield was 25.27 to 11.32 g / plant in healthy plants and 10.18 to 4.47 g / plant in infested plants. The reduction in estimated seed yield due to infestation by C. reflexa ranged from 14.04 to 30.07 per cent. One hundred per cent infestation reduced the seed yield by 31.21 to 71.52 per cent.